Can we forecast poor outcome in herpes simplex and varicella zoster encephalitis? A narrative review - Abbuehl, Lena S.; Hofmann, Eveline; Hakim, Arsany; Dietmann, Anelia (Frontiers in Neurology, 2023)
Herpes simplex virus (HSV) and varicella zoster virus (VZV) are among the most commonly diagnosed infectious causes of sporadic encephalitis worldwide. Despite treatment, mortality and morbidity rates remain high, especially for HSV encephalitis. This review is intended to provide an overview of the existing scientific literature on this topic from the perspective of a clinician who is confronted with serious decisions about continuation or withdrawal of therapeutic interventions. We performed a literature review searching two databases and included 55 studies in the review. These studies documented or investigated specifically outcome and predictive parameters of outcome of HSV and/or VZV encephalitis. Two reviewers independently screened and reviewed full-text articles meeting the inclusion criteria. Key data were extracted and presented as a narrative summary. Both, HSV and VZV encephalitis have mortality rates between 5 and 20% and complete recovery rates range from 14 to 43% for HSV and 33 to 49% for VZV encephalitis. Prognostic factors for both VZV and HSV encephalitis are older age and comorbidity, as well as severity of disease and extent of magnetic resonance imaging (MRI) lesions on admission, and delay in treatment initiation for HSV encephalitis. Although numerous studies are available, the main limiting factors are the inconsistent patient selection and case definitions as well as the non-standardised outcome measures, which hampers the comparability of the studies. Therefore, larger and standardised observational studies applying validated case definitions and outcome measures including quality of life assessment are required to provide solid evidence to answer the research question.